Influence of Students' Prior Knowledge and Classroom Learning Environment on Self-efficacy and Achievement in Mathematics - Aluri, Venkata Lakshmi Narayana (Curtin University, 2018)
I validated a 56-item seven-scale mathematics learning environment survey and used it to quantify the joint influence of students’ prior knowledge and classroom learning environment on achievement when mediated by self-efficacy. The joint influence was significant only for high-ability students, whereas the direct and mediated effects of prior knowledge were significant for medium- and low-ability students. A tool was developed for teachers to identify for remedial counselling students who over-assume their capabilities of mathematics achievement.